Disaggregating the international business cycle - Robert Gilhooly; Martin Weale; Tomasz Wieladek (Bank of England, External Monetary Policy Committee Unit, 2012)
This paper investigates the international business cycle with new sector level data on hours and output for Canada, Germany, France, Italy, the United Kingdom and the United States from 1992 Q1 to 2011 Q3. We estimate a Bayesian dynamic common factor model on this disaggregate data to decompose the quarterly growth rates of output, hours worked and labour productivity into contributions from global, country, sector and idiosyncratic factors. During the Great Recession our results suggest that the global factor became the most important determinant of output, hours and labour productivity growth. Before the Great Recession, on the other hand, the global factor was not very important; country and idiosyncratic factors were the dominant influences on output, hours and productivity; sector factors never matter very much.
Keywords: F44; 330; Labour productivity; international business cycles; dynamics common factor model